PEMBERDAYAAN IBU-IBU JAMAAH MAJELIS TA’LIM MELALUI PELATIHAN KEWIRAUSAHAAN SYARI’AH DI DESA BALOKANG KOTA BANJAR PROPINSI JAWA BARAT - Bisri, Hasan; Setiawan, Cucu (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2019)
Community service using the participatory action research (PAR) method offers a Shari'ah entrepreneurship training program. The activity carried out in Balokang Village, Banjar City, West Java Province succeeded in increasing the knowledge, understanding, and insights of the assembly members of the Assembly of Ta'lim about the Shari'ah economic theory, so that they have an awareness to do it in Shari'ah